Porcine Milk Oligosaccharides and Sialic Acid Concentrations Vary Throughout Lactation - Mudd, Austin T.; Salcedo, Jaime; Alexander, Lindsey S.; Johnson, Stacey K.; Getty, Caitlyn M.; Chichlowski, Maciej; Berg, Brian M.; Barile, Daniela; Dilger, Ryan N. (Frontiers in Nutrition, 2016)
Background Milk oligosaccharides (OSs) are bioactive components known to influence neonatal development. These compounds have specific physiological functions acting as prebiotics, immune system modulators, and enhancing intestine and brain development. Objectives The pig is a commonly used model for studying human nutrition, and there is interest in quantifying OS composition of porcine milk across lactation compared with human milk. In this study, we hypothesized that OS and sialic acid (SA) composition of porcine milk would be influenced by stage of lactation. Methods Up to 250 mL of milk were collected from seven sows at each of three time points: day 0 (colostrum), days 7–9 (mature), and days 17–19 (weaning). Colostrum was collected within 6 h of farrowing and 3-day intervals were used for mature and weaning milk to ensure representative sampling. Milk samples were analyzed for OS profiles by Nano-LC Chip–QTOF MS, OS concentrations via HPAEC-PAD, and SA (total and free) was assessed by enzymatic reaction fluorescence detection. Results Sixty unique OSs were identified in porcine milk. Neutral OSs were the most abundant at each lactation stage (69–81%), followed by acidic-sialylated OSs (16–29%) and neutral-fucosylated OSs (2–4%). As lactation progressed, acidic OSs decreased (P = 0.003), whereas neutral-fucosylated (P < 0.001) and neutral OSs (P = 0.003) increased throughout lactation. Six OSs were present in all samples analyzed across lactation [lacto-N-difucohexaose I (LNDFH-I), 2′-fucosyllactose (2′-FL), lacto-N-fucopentaose I (LNFP-I), lacto-N-neohexaose (LNnH), α1-3,β-4-d-galactotriose (3-Hex), 3′-sialyllactose (3′-SL)], while LDFT was present only in colostrum samples. Analysis of individual OS concentrations indicated differences (P = 0.023) between days 0 and 7. Conversely, between days 7 and 18, OS concentrations remained stable with only LNnH (P < 0.001) and LNDFH-I (P = 0.002) decreasing over this period. Analysis of free SA indicated a decrease (P < 0.001) as lactation progressed, while bound (P < 0.001) and total (P < 0.001) SA increased across lactation. Conclusion Concentrations of OS differ between colostrum and mature milk in the pig, and SA concentrations shift from free to bound forms as lactation progresses. Our results suggest that although porcine milk OS concentration and the number of structures is lower than human milk, the OS profile appears to be closer to human milk rather than to bovine milk, based on previously published profiles.